Inhibition of the oxygen-sensing asparaginyl hydroxylase factor inhibiting hypoxia-inducible factor: a potential hypoxia response modulating strategy - Wu, Y; Li, Z; McDonough, MA; Schofield, CJ; Zhang, X (American Chemical Society, 2021)
Factor inhibiting hypoxia-inducible factor (FIH) is a JmjC domain 2-oxogluarate and Fe(II)-dependent oxygenase that catalyzes hydroxylation of specific asparagines in the C-terminal transcriptional activation domain of hypoxia-inducible factor alpha (HIF-α) isoforms. This modification suppresses the transcriptional activity of HIF by reducing its interaction with the transcriptional coactivators p300/CBP. By contrast with inhibition of the HIF prolyl hydroxylases (PHDs), inhibitors of FIH, which accepts multiple non-HIF substrates, are less studied; they are of interest due to their potential ability to alter metabolism (either in a HIF-dependent and/or -independent manner) and, provided HIF is upregulated, to modulate the course of the HIF-mediated hypoxic response. Here we review studies on the mechanism and inhibition of FIH. We discuss proposed biological roles of FIH including its regulation of HIF activity and potential roles of FIH-catalyzed oxidation of non-HIF substrates. We highlight potential therapeutic applications of FIH inhibitors.